Phraseological Units in the Italian Novel "Io non ho paura" by Niccolò Ammaniti and Their Equivalents in the Serbian Translation - Blatešić, Aleksandra R.; Vujović, Marija N. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines phraseological units in the Italian novel Io non ho paura by Niccolò Amaniti and their equivalents in its Serbian translation Ne bojim se. The translation of phraseological expressions poses a distinct challenge within translation studies, primarily due to the idiomatic and expressive nature of these linguistic units. the optimal approach involves rendering phraseological units in the source text (ST) with corresponding units in the target text (TT), it is frequently necessary to employ specific translation strategies to ensure adequate transfer of meaning and stylistic nuance. Therefore, the aim of this study is to identify, through contrastive analysis, the translation techniques and strategies applied in the rendering of phraseological units. The corpus comprises Italian and Serbian phraseological units excerpted from the original novel and its translation, with examples categorized according to Mona Baker’s classification of translation strategies (2001). The analysis indicates that, in most cases, the translator employed the strategy of creating or introducing phraseological units that did not exist in the ST. This choice may reflect an effort to enhance the expressive quality of the translation, aligning with the stylistic tendencies of Ammaniti’s prose. Semantic equivalents—phraseological units of similar meaning but differing form—and strategies involving paraphrase or single-word translation were frequently employed, even when phraseological equivalents existed in the TT. These were followed by loan translations and absolute equivalents, i.e., units with both similar meaning and form. These were followed by loan translations and absolute equivalents, i.e., units with both similar meaning and form. In fewer cases, paraphrase or single-word translation was used due to the absence of corresponding phraseological units in the TT, supporting the hypothesis that typologically distinct languages such as Italian and Serbian may nonetheless share common phraseological features. The least frequent strategy involved translating phraseological units with other phraseological units that did not represent their most precise lexical and formal counterparts.
Keywords: translation strategies; phraseological units; equivalence; contemporary Italian novel; Niccolò Ammaniti; Italian; Serbian